MEHP induces alteration of mitochondrial function and inhibition of steroid biosynthesis in MA-10 mouse tumor Leydig cells. (November 2021) - Traore, Kassim; More, Prajakta; Adla, Akhil; Dogbey, Godwin; Papadopoulos, Vassilios; Zirkin, Barry
Highlights: MEHP exposure inhibits progesterone production by MA10 Leydig cells. MEHP up-regulates MA-10 cell mitochondria-derived ROS generation. Decrease in progesterone production by MA-10 cells correlates with reductions in STAR and CYP11A1 protein levels. Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is a plasticizer that is widely used in manufacturing. Previous studies have shown that mono-(2-ethylhexyl) phthalate (MEHP), the active metabolite of DEHP, has inhibitory effects on luteinizing hormone (LH)-stimulated steroid biosynthesis by Leydig cells. The molecular mechanisms underlying its effects, however, remain unclear. In the present study, we examined the effects of MEHP on changes in mitochondrial function in relationship to reduced progesterone formation by MA-10 mouse tumor Leydig cells. Treatment of MA-10 cells with MEHP (0–300 μM for 24 h) resulted in dose-dependent inhibition of LH-stimulated progesterone biosynthesis. Biochemical analysis data revealed that the levels of the mature steroidogenic acute regulatory protein (STAR), a protein that works at the outer mitochondrial membrane to facilitate the translocation of cholesterol for steroid formation, was significantly reduced in response to MEHP exposures. MEHP also caused reductions in MA-10 cell mitochondrial membrane potential (Δ Ψm ) and mitochondrial respiration as evidenced by decreases in the ability of the mitochondria to consume molecular oxygen. Additionally, significant increases in the generation of mitochondrial superoxide were observed. Taken together, these results indicate that MEHP inhibits steroid formation in MA-10 cells at least in part by its effects on mitochondrial function.